AGROECOLOGY IN ACTION: DESIGNING FARMING SYSTEMS THAT BALANCE ECOLOGICAL INTEGRITY AND AGRICULTURAL PRODUCTIVITY - Fatima Ali; Mahamat Saleh; Nadia Assingar (Techno Agriculturae Studium of Research, 2026)
Agroecology has emerged as a transformative approach to address the growing challenges of environmental degradation, climate variability, and declining sustainability in conventional agricultural systems. Intensive farming practices have often prioritized short-term productivity at the expense of ecological integrity, leading to soil degradation, biodiversity loss, and reduced system resilience. This study aims to analyze how agroecological principles can be operationalized in the design of farming systems that simultaneously maintain ecological integrity and enhance agricultural productivity. The research employed a mixed-methods approach combining field-based comparative analysis of agroecological and conventional farming systems, ecological assessments, and secondary data review. Key indicators included crop yield, soil health parameters, biodiversity indices, input-use efficiency, and ecosystem service provision. The results indicate that agroecological farming systems achieved comparable or higher productivity levels than conventional systems while significantly improving soil quality, biodiversity, and resource-use efficiency. Enhanced ecological interactions, such as nutrient cycling and biological pest regulation, contributed to system stability and reduced dependency on external inputs. The study concludes that agroecology provides a viable framework for designing resilient farming systems capable of balancing productivity with ecological sustainability. Adoption of agroecological practices represents a strategic pathway toward sustainable food systems, ecosystem conservation, and long-term agricultural resilience.